2012
DOI: 10.3174/ajnr.a3054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Characteristics of Multiple Dural Arteriovenous Shunts

Abstract: BACKGROUND AND PURPOSE:The pathogenesis and characteristics of multiple DAVSs are not wellknown. The purpose of this study was to evaluate the angiographic and clinical characteristics of patients with multiple DAVSs with an emphasis on the pathomechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Only a few cases have been published in the past 15 years; therefore, the pathogenesis, presentation, clinical course, and treatment remain unclear. 4,[8][9][10][11][12] The purpose of this single-institution retrospective cohort study was to compare the clinical characteristics, angioarchitecture, and treatment outcomes of patients with progressive (enlarging fistulas or developing de novo fistulas) versus nonprogressive (recurrent original fistula or the presence of multiple unchanging fistulas) intracranial DAVFs.…”
mentioning
confidence: 99%
“…Only a few cases have been published in the past 15 years; therefore, the pathogenesis, presentation, clinical course, and treatment remain unclear. 4,[8][9][10][11][12] The purpose of this single-institution retrospective cohort study was to compare the clinical characteristics, angioarchitecture, and treatment outcomes of patients with progressive (enlarging fistulas or developing de novo fistulas) versus nonprogressive (recurrent original fistula or the presence of multiple unchanging fistulas) intracranial DAVFs.…”
mentioning
confidence: 99%
“…Finally, one should be aware of the potential for both synchronous and metachronous separate dAVFs which, although rare, are more commonly seen in association with an aggressive presentation and may need to be addressed at another time as in our case [7].…”
Section: Discussionmentioning
confidence: 90%
“…In some cases, multiple lesions are simultaneously found at the time of diagnosis and this is generally called multiple DAVFs. Recent studies revealed that these synchronous multiple lesions are found in 7~8% of intracranial DAVFs [3, 18]. On the other hand, second DAVF development in another sinus after resolution of the first lesion is rare.…”
Section: Discussionmentioning
confidence: 99%